![\frac{1}{3} (x - y) = \frac{1}{4} (y - 1) \\ \frac{1}{7} (4x - 5y) = x - 7 \frac{1}{3} (x - y) = \frac{1}{4} (y - 1) \\ \frac{1}{7} (4x - 5y) = x - 7](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B3%7D+%28x+-+y%29+%3D++%5Cfrac%7B1%7D%7B4%7D+%28y+-+1%29+%5C%5C++%5Cfrac%7B1%7D%7B7%7D+%284x+-+5y%29+%3D+x+-+7)
pls solve the above equations with simultaneously methods
pls help me
Answers
Answered by
1
Answer:
x = 8
y = 5
Step-by-step explanation:
(4x - 7y = -3) × 5 ----- (i)
20x - 35y = -15 ----- (ii)
(3x + 5y = 49) ----- × 7 (iii)
21x + 35y = 343 ----- (iv)
Add (ii) and (iv)
20x - 35y + 21x + 35y = -15 + 343
41x = 328
x = 328/41
x = 8
20x - 35y = -15
20(8) - 35y = -15
160 - 35y = -15
35y = 175
y = 175/35
y = 5
Answered by
0
Answer:
upside your answer
okay mark me as brainliest
Similar questions